Trends in Ultrasound Use in Low and Middle Income Countries: A Systematic Review - Kelsey A. Stewart, MD; Sergio M. Navarro, MBA; Sriharsha Kambala, BS; Gail Tan, BS; Revanth Poondla, BS; Sara Lederman, BS; Kelli Barbour, MD; Chris Lavy, MD (Global Health and Education Projects, Inc., 2020)
Background: Evidence on recent trends regarding the impact and cost-benefits of ultrasound in resource-constrained settings is limited. This study presents a systematic review to determine recent trends in the utility and applicability of ultrasound use in low and middle income countries (LMIC). The review includes characterizing and evaluating trends in (1) the geographic and specialty specific use of ultrasound in LMICs, (2) the innovative applications and the accompanying research findings, and (3) the development of associated educational and training programs. Methods: The electronic databases Medline OVID, EMBASE, and Cochrane were searched from 2010 to 2018 for studies available in English, French, and Spanish. Commentaries, opinion articles, reviews and book chapters were excluded. Two categories were created, one for reported applications of ultrasound use in LMICs and another for novel ultrasound studies. Results: A total of 6,276 articles were identified and screened, 4,563 studies were included for final review. 287 studies contained original or novel applications of ultrasound use in LMICs. Nearly 70% of studies involved ultrasound usage originating from Southeast Asia and sub-Saharan Africa, the latter being the region with the highest number of innovative ultrasound use. Educational studies, global collaborations, and funded studies were a substantial subset of overall ultrasound research. Our findings are limited by the lack of higher quality evidence and limited number of randomized clinical trials reported. Conclusion/Global Health Implications: Our systematic literature review of ultrasound use in LMICs demonstrates the growing utilization of this relatively low-cost, portable imaging technology in low resource settings. Key words: • Ultrasound • Ultrasonography • Echocardiogram • LMIC • Low resource • Global health • Systematic review   Copyright © 2020 Stewart et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.